KELAYAKAN FINANSIAL USAHA PERIKANAN HUHATE DI KECAMATAN SAPARUA KABUPATEN MALUKU TENGAH - Febrian H. Tanamal (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2020)
Saparua is a district in Central Maluku Regency which has 8 units of huhate (pole and line) fishing fleet and can be operated throughout the season. This condition shows that this business should be able to provide benefits, both for the owners and fishermen. However, the utilizing of skipjack resources that have exceeded the MSY value and also the substantial operational costs cause income to decline. Therefore this study aims to analyze the financial feasibility of the pole and line fisheries business in Saparua District. A survey for 5 pole and line business units in Saparua was conducted to obtain data, which were then analyzed by using several investment criteria such as NPV (Net Present Value), IRR (Internal Rate of Return), and B / C (Benefit Cost Ratio). The results show that: 1). The implementation of business management is still simple, but the tasks division among fishermen is clear. The decision is generally made by the owner. The frequency of fishing depends on the fishing season. During the west season, the fishing ground is in Banda Sea to the southern part of Seram Sea, while in the eastern season is in the northern part of Seram Sea; 2). Based on the pattern of revenue sharing, the average fishermen's income / month is lower than the minimum wage provincial (UMP) in Maluku; and 3). The highest economic benefit is achieved by the 4th pole and line unit, as well as the B / C Ratio criteria index so that it becomes a development priority because B / C Ratio shows the comparison of sacrifice (output) and results (input).